Critical Thinking in Science Learning: Systematic Literature Review - Santri Ramadani; Parlindungan Sinaga; Winny Liliawati (Jurnal Pemberdayaan Masyarakat, 2025)
Critical thinking is a vital intellectual skill that enables informed judgments through the analysis of information. Its development in educational settings is essential, particularly in science learning, where analytical reasoning and problem-solving are fundamental. This study aims to analyze Scopus-indexed journal articles (Q1–Q4) that investigate critical thinking in science education. A systematic literature review process was employed to examine 57 empirical papers, encompassing three primary stages: planning, conducting, and reporting. The analysis examined research areas, subject fields, participants, data collection tools, and research methods. The results indicated that most studies employed a quantitative approach, with high school students from medium-sized schools as the primary participants. Essay tests were the most commonly used instruments for measuring critical thinking. The primary research emphasis was on creating and assessing instructional materials, particularly within the realm of physics education. These findings reveal current trends and research gaps, particularly in underexplored topics such as cross-disciplinary integration and assessment strategies. This study contributes to science education by mapping the current research landscape of critical thinking and providing insights that inform future investigations, curriculum design, and instructional innovation.